The Descriptive Analysis of TPACK Components in Chemistry Learning Tools for The Electrolyte and Non-electrolyte Solutions Materials - Rifanny Rizka Putri; Muhaimin Muhaimin; Sutrisno Sutrisno (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2021)
Electrolyte and non-electrolyte solutions were chemical materials that had three levels of representation. However, during the learning process there were still many learning difficulties. One of the factors that students experience difficulty in learning was that teachers were not optimal in planning lessons. However, in the process of achieving learning objectives, it was necessary to had optimal learning planning. One of the optimal learning plans was obtained by preparing learning instruments such as lesson plans and e-LKPD which integrated TPACK. This research was a descriptive study which aims to analyzed descriptively the TPACK components in the developed chemistry learning tools. The data collection techniques in this study used document study techniques, interviews, and surveys. The data instruments used in obtaining information were questionnaires, interview guideline sheets, and previous articles. Researchers took samples by purposive sampling. The research subjects were students and teachers of class X IPA SMA in Jambi City. Based on the analysis conducted by researchers through data collection instruments, it can be concluded that this learning tool has integrated Technology, Pedagogic, and Content Knowledge components.